O Ensino da Matemática Financeira Utilizando a Calculadora HP 12C - Oliveira, Mayana Cybele Dantas de (2014)
This research has as object of study the teaching of Financial Mathematics, with the aid of a tool: the Financial Calculator HP 12C, preparing citizens able to manage their own budgets and the labor market. Preliminary concepts concerning the theme are presented, followed by examples in context, pointing out the main factors that facilitate the understanding of each content. Being approached through practical applications, which makes learning easier, and increases motivation and students' interest.